2009
DOI: 10.1016/j.neuroimage.2008.12.057
|View full text |Cite
|
Sign up to set email alerts
|

Age and diffusion tensor anisotropy in adolescent and adult patients with schizophrenia

Abstract: Findings of white matter pathology as indicated by diffusion tensor anisotropy values in schizophrenia are well established, but the differences in this measure between the onset of the disease and the chronic state are not well known. To investigate the differences between these states in the progression of the disease of schizophrenia we acquired 1.5 T diffusion tensor anisotropy images on 35 adult patients with schizophrenia and schizoaffective disorder, 23 adolescents having their first psychotic episode, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
48
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(52 citation statements)
references
References 25 publications
4
48
0
Order By: Relevance
“…Adolescent ( n =17) and adult schizophrenia patients ( n =34) and age- and sex-matched healthy controls ( n =15 and n =33, respectively) were recruited as described elsewhere (Schneiderman et al, 2009; see Table-1 for demographic information). Only those adolescents who ultimately received a diagnosis of schizophrenia were included in the current study.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Adolescent ( n =17) and adult schizophrenia patients ( n =34) and age- and sex-matched healthy controls ( n =15 and n =33, respectively) were recruited as described elsewhere (Schneiderman et al, 2009; see Table-1 for demographic information). Only those adolescents who ultimately received a diagnosis of schizophrenia were included in the current study.…”
Section: Methodsmentioning
confidence: 99%
“…Studying antipsychotic drug-naĂŻve adolescent patients affords the opportunity to examine potential neurological abnormalities in this patient population without the influence of prolonged exposure to antipsychotic medication and/or hospitalization. To date, only one study has examined corpus callosum abnormalities in antipsychotic drug-naĂŻve adolescent patients using stereotaxically-located regions of interest and reported no differences in anisotropy (Schneiderman et al, 2009). The current study improves on this research by using manually-traced regions-of-interest (the gold standard) and examining the corpus callosum in its near entirety.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some cross-sectional studies have found that WM deficits in chronic patients were either absent or less severe than in FE patients (25, 33, 34), and a meta-analysis of FE and multi-episode studies showed that longer duration of illness was associated with more severe WM abnormalities (35). Similarly, research comparing patients with either adolescent or adult onset psychosis has shown that age of onset may impact the degree of WM impairment (36–38). …”
Section: Open Questions and Future Directionsmentioning
confidence: 99%
“…Furthermore, genetic analyses in COS patients have shown that carriers of a neuregulin-1 risk allele had a steeper rate of decline in WM volume during adolescence, compared to patients without the risk allele (Addington et al, 2007). Studies comparing adolescent and chronic patients identified effects of age of onset, and suggest that prefrontal FA deficits develop when illness onset occurs at a later age (Kyriakopoulos et al, 2009; Schneiderman et al, 2009). …”
Section: White Matter Development In Schizophreniamentioning
confidence: 99%